Comparing Injectable DaxibotulinumtoxinA and OnabotulinumtoxinA in Moderate and Severe Glabellar Lines: Additional Analyses From a Phase 2, Randomized, Dose-Ranging, Double-Blind, Multicenter Study. (December 2017) - Bertucci, Vince; Humphrey, Shannon; Carruthers, Jean; Solish, Nowell; Muhn, Channy; Swift, Arthur; Rubio, Roman G.; Shears, Gill; Rosen, Nathan
Abstract : BACKGROUND: Injectable daxibotulinumtoxinA (RT002) is an investigational botulinum toxin Type A. Published Phase 2 data show that, compared with 20U onabotulinumtoxinA, 40U daxibotulinumtoxinA is associated with a significantly greater response rate and significantly longer duration of response (median 24 weeks), and appears generally safe and well tolerated (www.clinicaltrials.gov NCT02303002). OBJECTIVE: To evaluate whether these efficacy and safety findings are influenced by baseline glabellar line severity. MATERIALS AND METHODS: In the Phase 2, randomized, dose-ranging, parallel-group, double-blind, multicenter study, subjects with moderate or severe glabellar lines at maximum frown were randomly assigned to 20U, 40U, or 60U daxibotulinumtoxinA, 20U onabotulinumtoxinA, or placebo. Efficacy was evaluated by investigators for ≥24 weeks. RESULTS: Data from the per protocol population ( n = 191) stratified by baseline glabellar line severity (125 moderate, 66 severe) suggest that the clinical advantage of 40U daxibotulinumtoxinA over 20U onabotulinumtoxinA is maintained for a range of efficacy outcomes regardless of whether glabellar lines are moderate or severe at baseline. Statistical evaluations were not completed due to the limited size of each subgroup. CONCLUSION: 40U daxibotulinumtoxinA appears to offer a clinical efficacy advantage over 20U onabotulinumtoxinA in both moderate and severe glabellar lines—with a greater advantage observed in severe glabellar lines.